Laparoscopy-Assisted Transgastric ERCP: A Challenging Technique for Biliary Clearance Post Roux-en-Y Gastric Bypass - Garg, Hitendra Kumar; Singh, Pankaj; Peters, Atul N. C.; Agarwal, Shalabh; Gautam, Yogesh; Mishra, Dhruv Kant (Journal of Digestive Endoscopy, 2021)
Biliary complications after Roux-en-Y gastric bypass (RYGB) are not uncommon. Managing choledocholithiasis in this subset of patients is challenging as conventional endoscopic retrograde cholangiopancreatography (ERCP) is not possible due to lack of peroral access to the second part of duodenum. Enteroscopic approach, however, theoretically feasible is difficult and cumbersome, often resulting in failed procedure. Small series has reported higher success with a novel technique of laparoscopic transgastric access for ERCP. Laparoscopy-assisted ERCP (LA-ERCP) is now increasingly being recognized as a safe and reliable technique for biliary clearance with a low complication rate, making it a preferred approach for managing biliopancreatic disease in these groups of patients. Here we report a case of a young patient with gallstone disease and choledocholithiasis presenting with obstructive jaundice post RYGB who was successfully managed by LA-ERCP followed by laparoscopic cholecystectomy in the same session.
Keywords: Roux-en-Y gastric bypass; RYGB; laparoscopy-assisted transgastric endoscopic retrograde cholangiopancreatography; LA-ERCP